Effect Of Job Analysis, Competency, And Compensation On Employee Performance - Ch Endah Winarti; YOHANES FERRY CAHAYA; Annathasia Puji Erasashanti; Hikmah Abdul Rachman; Bongsu Kurniawan (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This study aims to determine and analyze the effect of job analysis, competency, and compensation on employee performance of Bureau of Organization and Governance Ministry of Finance. The population of this study were all employees of the Bureau of Organization and Management. The independent variables in this study are job analysis, competence, and compensation, while the dependent variable in this study is employee performance. This study uses a descriptive method with a quantitative approach. The sampling technique used is saturated sampling with a total of 55 employees. Sources of data obtained from the results of the distribution of questionnaires with the analytical technique used is multiple linear regression analysis with the help of the SPSS for mac version 28 statistical program. The results show that (1) Position Analysis has a negative and significant effect on employee performance; (2) Competence has a positive and significant effect on employee performance; (3) Compensation has a positive and significant effect on employee performance